Moral disengagement and the harms of cocaine use. (3rd September 2022) - Sumnall, Harry R.; Montgomery, Catharine; Atkinson, Amanda M.; Gage, Suzanne H.; Boardley, Ian D.
Abstract: There has been recent UK media attention on the global impact of the cocaine trade and the morality of personal use of cocaine powder. In this study we investigated whether people who use cocaine engage in moral disengagement (MD) strategies to reduce anticipated guilt associated with use. Participants read text describing the impact of the global cocaine market on others and completed a range of measures including assessments of substance use, MD, anticipated guilt, internalised moral identity, and empathy. We hypothesised that cocaine-related MD would positively predict cocaine use, and this would be partly mediated by anticipated guilt. Complete data were obtained from 254 participants through an anonymous cross-sectional survey (59.8% Female; mean age 30.8 ± 12.6 years). Our hypotheses were supported; (i) MD predicted cocaine use positively and anticipated guilt negatively; (ii) anticipated guilt negatively predicted cocaine use; anticipated guilt partially mediated the relationship between MD and cocaine use. People who use powder cocaine may use MD to reduce the anticipated guilt associated with knowledge of the harms associated with the drugs trade. Campaigns that focus on the morality of cocaine use or ethical choices may therefore have limited impact unless MD is challenged as part of these campaigns.